Trophic relationships of exotic anadromous salmonids in the southern Patagonian Shelf as inferred from stable isotopes - Ciancio Blanc, Javier Ernesto (2008)
On the basis of their thermal preferences, salmon introduced in South America can distribute over the whole Southern Patagonian Shelf Ecosystem (SPSE). Stable isotope (δ13C and δ15N) data show that the SPSE is dominated by zooplanktivorous species (15 of 37), and its community is distributed over six trophic levels (TL), with salmonids occupying levels 4.2 to 4.9. A dual isotope mixing model was used to estimate diet proportions of adult salmonids (validated with stomach content analyses) and showed that chinook salmon (TL 4.9) and brown trout (TL 4.7) feed largely on sprats (96% and 79% predicted by the model) and were clustered together with intermediate size fish and cephalopod predators (TL 4.6-5), a diet similar to that in their native ranges (North Pacific and North Atlantic Oceans). Adult anadromous rainbow trout clustered together with zooplanktivorous species (TL 3.2-4.4), and the model predicted a diet dominated by planktonic crustaceans (55%), very different from the diet dominated by fish and squids characteristic of adult steelhead in the North Pacific Ocean. Diet predictions based on stable isotopes for Chinook salmon were indistinguishable from direct assessments of stomach contents of fish captured by bottom trawlers and overlapped widely with the diet of Magellanic penguins. The lack of reports on captures of anadromous rainbow trout by bottom trawlers suggests that this species has a shallower distribution. Stable isotope data for rainbow trout are very similar to those of rockhopper penguins, which feed on planktonic crustaceans, fish larvae, and juveniles.